Integrated transcriptomics and metabolomics to explore the varied hepatic toxicity induced by aged- and pristine-microplastics: in vivo and human-originated liver organoids-based in vitro study - Cheng, Wei; You, Yifei; Chen, Hange; Zhou, Yue; Feng, Yan; Wang, Yan (Environmental research, 2025)
Microplastics (MP) have distributed ubiquitously and emerged as a significant health risk to human beings. The adverse effect induced by aged MP at concentrations being equivalent to human internal exposure level, has raised special concern, however, is still unclear. In this study, human embryonic stem cells-derived liver organoids (LOs), a novel three-dimensional in vitro model, were exposed to 75 ng/mL self-made polypropylene (PP) and aged PP (aPP), following UV-photoaging for 0- and 500-h respectively, were subject to transcriptomic and metabolomic analysis individually and jointly, to explore the potential adverse effect of PP and aPP on human liver. The mean size of PP and aPP were 7.60 and 6.91 μm, with rough and irregular surface, and varied carbonyl index (CI) (0.08 and 0.25 respectively), indicating there were distinguished physicochemical properties. Transcriptomic analysis suggested the NADH dehydrogenase at mitochondrial complex and ATP synthesis maybe more sensitive to aPP, rather than PP. Metabolomic analysis enriched KEGG pathways including cysteine (Cys) and methionine metabolism significantly. Collectively, the homocysteine (Hcy) metabolism, were anchored upon integrated analysis. To validate, the changes in NADH dehydrogenase-encoding genes, activities of complexs, mitochondrial membrane potential, Hcy and Cys contents, as well, the cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE), were detected both in vitro and in vivo. Finally, increased serum Cys and decreased hepatic Cys were confirmed, without inflammation in the liver. The peripheral Hcy may serve as a potential biomarker for indicating the MP-induced systematic adverse health outcomes, due to the disturbance in the Hcy metabolism in the liver. •Aged MP could disrupt homocysteine metabolism in vitro and in vitro in liver.•The dose used was equivalent to human internal exposure level.•Aged-and pristine MP used were mixed-size equal to human internal exposure case.•Increase in serum homocysteine induced by aged MP maybe a potential biomarker.•Enzymes involved in the homocysteine metabolism were suppressed by aged MP.